Valorisation of vegetable oils via metathesis reactions on solid catalysts: Cross-metathesis of methyl oleate with 1-hexene - Zelin, Juan (2015)
Abstract The activity and selectivity of silica-supported Hoveyda-Grubbs (HG) complex for the cross-metathesis of methyl oleate with 1-hexene to obtain 1-decene, methyl 9-tetradecenoate, 5-tetradecene and methyl 9-decenoate were studied in a batch reactor. The HG complex loading was varied between 0.87 and 11.6 wt%. Competitive secondary reactions were the self-metathesis of methyl oleate and the self-metathesis of 1-hexene. The yield to cross-metathesis products (ηC-M) was 47% when a 1-hexene/methyl oleate reactant ratio (RC6/MO) of one was employed. The ηC-M value increased with increasing 1-hexene initial concentration, reaching 87% for RC6/MO = 7. The selectivity to terminal olefins also increased at the expense of internal olefins among the cross-metathesis products when the concentration of 1-hexene was increased.